Effects of inoculation of corn silage with Lactobacillus hilgardii and Lactobacillus buchneri on silage quality, aerobic stability, nutrient digestibility, and growth performance of growing beef cattle - Nair, Jayakrishnan (2020)
This study evaluated the effects of inoculation of whole crop corn silage with a mixture of heterofermentative lactic acid bacteria (LAB) composed of Lactobacillus hilgardii and Lactobacillus buchneri on ensiling, aerobic stability, ruminal fermentation, total tract nutrient digestibility, and growth performance of beef cattle. Uninoculated control corn silage (CON) and silage inoculated with 3.0 × 105 cfu g-1 of LAB containing 1.5 × 105 cfu g-1 of L. hilgardii CNCM I-4785 and 1.5 × 105 cfu g-1 of L. buchneri NCIMB 40788 (INOC) were ensiled in silo bags. The pH did not differ (P > 0.05) between the two silages during ensiling but was greater (P < 0.001) for CON than INOC after 14 d of aerobic exposure (AE). Neutral detergent insoluble crude protein (NDICP) content (% of DM and % of CP basis) of terminal INOC silage was greater (P ≤ 0.05) than that of CON. In terminal silage, concentrations of total VFA and acetate were greater (P < 0.001), while water-soluble carbohydrates were lower (P < 0.001) for INOC than CON. Yeast and mold counts were lower for INOC than CON (P ≤ 0.001) in both terminal and aerobically exposed silages. The stability of INOC was greater (P < 0.001) than that of CON after 14 d of AE. Ruminal fermentation parameters and DMI did not differ (P > 0.05) between heifers fed the two silages, while there was a tendency (P ≤ 0.07) for lower CP and starch digestibility for heifers fed INOC than CON. Total nitrogen (N) intake and N retention were lower (P ≤ 0.04) for heifers fed INOC than CON. Dry matter intake as a percentage of BW was lower (P < 0.04) and there was a tendency for improved feed efficieny (G:F; P = 0.07) in steers fed INOC vs. CON silage. The NEm and NEg contents were greater for INOC than CON diets. Results indicate that inoculation with a mixture of L. hilgardii and L. buchneri improved the aerobic stability of corn silage. Improvements in G:F of growing steers fed INOC silage even though the total tract digestibility of CP and starch tended to be lower for heifers fed INOC are likely because the difference in BW and growth requirements of these animals impacted the growth performance and nutrient utilization and a greater proportion of NDICP in INOC than CON.